North Atlantic ventilation using chlorofluorocarbons and idealised-tracer simulations - He, Yan-Chun; Gao, Yongqi; Bentsen, Mats; Tan, Benkui; Johannessen, Ola. M. (Tellus B: Chemical and Physical Meteorology, 2012)
The simulated chlorofluorocarbon CFC-11 and 29 geographically defined CFC-11 tracers, as well as 29 geographically defined idealised tracers, are used to quantify the regional contribution to the ventilation of the North Atlantic Ocean in a global version of the Miami Isopycnal Coordinate Ocean Model (MICOM) driven by the daily NCEP/NCAR forcing. Age tracers attached to 29 idealised tracers are also used to estimate the timescales for the water masses' transports. Our results show that the simulated overturning circulation matches the available observed data for both intensity and variability, and the simulated distribution of CFC-11 concentration in the subtropical North Atlantic Ocean is in good agreement with the observations, particularly above 800 m in depth. We found that the sandwich-like distribution of CFC-11 concentration in the subtropical North Atlantic in both the observations and simulations is mainly caused by subduction from the western and eastern subpolar North Atlantic, but the contribution of the former (56.0%) is almost four times larger than that of the latter (15.7%). We demonstrated that the ocean dynamics, instead of the source function, determine the annual and inter-annual variability in both dynamically active tracer (such as water temperature and salinity) and passive tracer (such as CFC-11 and idealised tracer) concentrations in the deep North Atlantic. The 'apparent age' distribution shows that the surface water in the western subpolar North Atlantic takes about 12 yr to reach the Nordic Seas and takes 20 yr from the Nordic Seas to the subtropical deep North Atlantic. The transit-time derived by 'optimum time lag' approach shows a 9.3-13.6 yr lag for the signals propagating from the western subpolar North Atlantic to the subtropical North Atlantic, which is generally consistent with that of about 10 yr derived from the 'apparent age'. The study suggests that geographically defined tracers can be used as an efficient tool to investigate the source and spreading pathway of water, and to forecast the spreading and spreading time of environmental accidents such as the radioactive waste in the world's oceans. http://gateway.webofknowledge.com/gateway/Gateway.cgi?GWVersion=2&SrcApp=PARTNER_APP&SrcAuth=LinksAMR&KeyUT=WOS:000310350300001&DestLinkType=FullRecord&DestApp=ALL_WOS&UsrCustomerID=8e1609b174ce4e31116a60747a720701 Meteorology & Atmospheric Sciences SCI(E) 0 ARTICLE null 64